TINGKAT PENGETAHUAN, PERAN PETUGAS KESEHATAN DAN PENERAPAN GERMAS DI RW 8 KELURAHAN KUBU MARAPALAM - Sidaria Sidaria; Ridha Hidayati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The world is currently experiencing health problems where the increase of mortality and morbidity become uncontrolable, one of the main causes is resulted by Non Communicable Diseases (NCD) such as stroke, hypertension, cancer and diabetes.the increase of NCD can reduce the productivity of human resources, even the quality of nation’s generation. to overcome this the government has launched a national movement through the instruction of Indonesian Presiden Number 1 in 2017. This movement is as known as Gerakan Masyarakat Hidup Sehat (GERMAS). This research aims to know related factor of knowledge level And role of health officer with application Gerakan Masyarakat Hidup Sehat (GERMAS) at RW 8 Kubu Marapalam sub-district working area of Andalas Public Health Center in 2018. Research design is analytic with cross-sectional approach. Sampling technique that is proportional random sampling of 73 family. The research was conducted on March-August 2018, and research instrument was questionnaire. Univariate analysis is in the form of distribution of frequency table and bivariate analysis is by using chi-square test. Result from this Research found 57.5% of families with poor application of GERMAS, 57.5% of families with low knowledge level, 53.4% of families with poor the role of health workers, there was significant correlation between level of knowledge with the application of GERMAS p = 0.000, there was significant correlation between The role of health workers with the application of GERMAS p = 0,000. It is recommended for health agencies in this case Andalas Public Health Center to make more significant efforts to improve the application of GERMAS to the community by doing counseling, activating the program keluarga binaan and activating Pos Pembinaan Terpadu (POSBINDU).